Crash severity effects of adaptive signal control technology: An empirical assessment with insights from Pennsylvania and Virginia. (March 2019) - Khattak, Zulqarnain H.; Fontaine, Michael D.; Smith, Brian L.; Ma, Jiaqi
Highlights: Crash severity effects of Adaptive signal control technology (ASCT) were assessed. Multiple ASCT systems deployed across Pennsylvania and Virginia were analyzed. Combined best fit model revealed reductions in severe plus moderate and minor injury crashes by 5.24% and 9.91%. Combined best fit model showed a low forecast error of 0.301 and was also observed to be spatially transferable. Abstract: Adaptive signal control technology (ASCT) is an intelligent transportation systems (ITS) technology that optimizes signal timings in real time to improve corridor flow. While a few past studies have examined the impact of ASCT on crash frequency, little is known about its effect on injury severity outcomes. Similarly, the impact of different types of ASCTs deployed across different states is also uncertain. This paper therefore, used ordered probit models with random parameters to estimate the injury severity outcomes resulting from ASCT deployment across Pennsylvania and Virginia. Two disparate systems deployed across the two different states were analyzed to assess whether they had similar impacts on injury severity, although signal timings are optimized using different algorithms by both systems. The estimation results revealed that both ASCT systems were associated with reductions in injury severity levels. Marginal effects showed that Type A ASCT systems reduced the propensity of severe plus moderate and minor injury crashes by 11.70% and 10.36% while type B ASCT reduced the propensity of severe plus moderate and minor injury crashes by 4.39% and 6.92%. Similarly, the ASCTs deployed across the two states were also observed to reduce injury severities. The combined best fit model also revealed a similar trend towards reductions in severe plus moderate and minor injury crashes by 5.24% and 9.91%. This model performed well on validation data with a low forecast error of 0.301 and was also observed to be spatially transferable. These results encourage the consideration of ASCT deployments at intersections with high crash severities and have practical implications for aiding agencies in making future deployment decisions about ASCT.